2015
DOI: 10.3349/ymj.2015.56.1.227
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism of the Renin Geners6682082Is Associated with Essential Hypertension Risk and Blood Pressure Levels in Korean Women

Abstract: PurposeThe aim of the present study was to investigate associations between the renin gene (REN) and the risk of essential hypertension and blood pressure (BP) levels in Koreans.Materials and MethodsTo outline the functional role of a single nucleotide polymorphism in the transcription of the REN gene, we conducted a case-control study of 1975 individuals: 646 hypertension (HT) patients and 1329 ethnically and age-matched normotensive subjects.ResultsLogistic regression analysis indicated that the genotypes AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Both mutations are found in the intracellular cytoplasmic tail of the receptor, near the 7 th transmembrane region, which is a probable Gs-protein binding domain [ 19 , 27 ]. Renin, a protease expressed mostly in the kidney, hence catalyses the first and rate-limiting step of the RAS cascade, playing an important role in the control of blood pressure and electrolyte balance [ 28 ]. The REN gene is made up of 12 exons spread across 12 kb of human chromosome 1q32 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both mutations are found in the intracellular cytoplasmic tail of the receptor, near the 7 th transmembrane region, which is a probable Gs-protein binding domain [ 19 , 27 ]. Renin, a protease expressed mostly in the kidney, hence catalyses the first and rate-limiting step of the RAS cascade, playing an important role in the control of blood pressure and electrolyte balance [ 28 ]. The REN gene is made up of 12 exons spread across 12 kb of human chromosome 1q32 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on candidate-gene-based association are still very popular for identifying genetic components of EH. 3 …”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Vangjeli et al 13 found that the REN-5312C/T polymorphism was associated with increased blood pressure in the Irish population. Park et al 3 suggested that carriers of the A allele in rs6682082 were more likely to have hypertension amongst Korean women. Another aspect of REN variation was insert/deletion ( I/D ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The REN single-nucleotide polymorphisms (SNPs) are found to be associated with risk of having the aforementioned diseases [5,6]. Some of these are studied in different populations such as Korea, Mexico, USA, and Europe [7,8]. rs5705 is an exonic synonymous variant whose frequency distribution is unavailable in Indian population.…”
mentioning
confidence: 99%